Multimodal Archipelago: Social Movement Knowledge Practices Among Transnational Rohingya - Cerretani, J. Francis (Annali di Ca’ Foscari: Serie Orientale)
This article aims to establish a conceptual framework around digital social movements in and of Myanmar (Burma) and the archipelagic affinities (Cuevas-Hewitt 2011) which complexly connect them. Archipelago represents how social movements, like islands, are both divided and connected through multidirectional waterways of staked arguments, and knowledge-sharing among different communities. This article argues that these (dis)connections are being (re)made in the aftermath of the attempted coup both on the internet and on the ground. Anti-military affinities, religious affiliations, and ethnonationalisms are part of the picture of Burma’s social movements. The knowledge practices of transnational Rohingya networks channel into other networked social movements in and of Myanmar. As individual Rohingya try to navigate around the state, a moral subject (Jirattikorn 2023) emerges within the imagined communities in Myanmar and in the digital diasporas. The (non)location of digital diasporas is where this article focuses. Drawing from the ethnographic fieldwork I conducted with the Rohingya Community in Ireland (RCI), their diasporic connections, and the interventions they make with the ongoing genocide in Myanmar, this article highlights the diffuse nature of intersecting, digital social movements to contribute towards understandings of how “complex connectivity” (Tomlinson 1999) can be viewed as a mobilising force against the military’s attempt at centralising power (Graeber 2004). With a framework built on indigenous and decolonial epistemologies (Magsalin 2020), I aim to trace the contours of these Archipelagic Affinities as bridging, straying, and fraying lines of flight (Deleuze, Guattari 1987) that complexly connect varying social movements and the communities entangled within. As the article draws towards a rupturing pangaea of rifting and drifting conclusions I find a commonality among the aspirations of transnational Rohingya networks and other social movements such as the CDM (Civil Disobedience Movement) and widespread community-run schools for people of Myanmar.  I engage with literature in multimodal anthropology, politics of care, networked social movement theory, and anarchist theory to centre on the everyday intimacies and labour that the transnational Rohingya communities I conducted fieldwork with use to: straddle the realms of the personal and political, make movements that critically engage with the stakes of their futures, and share their knowledge practices through the internet. The etymology of affinity, with the latin ad- finis meaning to border, and affinis meaning related, is a useful simulacrum of how points of separation are also points of connection among Rohingya movements with the multifarious social movements in and of Myanmar.